Piezo channels in the intestinal tract - Haolong He; Jingying Zhou; Xuan Xu; Pinxi Zhou; Huan Zhong; Huan Zhong; Mi Liu; Mi Liu (Frontiers in Physiology, 2024)
The intestine is the largest mechanosensitive organ in the human body whose epithelial cells, smooth muscle cells, neurons and enteroendocrine cells must sense and respond to various mechanical stimuli such as motility, distension, stretch and shear to regulate physiological processes including digestion, absorption, secretion, motility and immunity. Piezo channels are a newly discovered class of mechanosensitive ion channels consisting of two subtypes, Piezo1 and Piezo2. Piezo channels are widely expressed in the intestine and are involved in physiological and pathological processes. The present review summarizes the current research progress on the expression, function and regulation of Piezo channels in the intestine, with the aim of providing a reference for the future development of therapeutic strategies targeting Piezo channels.